Fundamentals of neurology an illustrated guide - Mattle, Heinrich (Thieme, 2017)
"The second edition of this practical guide provides a thorough introduction to the essential concepts of clinical neurology. Coverage includes history-taking; the neurological examination and ancillary tests; topical diagnosis and differential diagnosis of typical syndromes; the diseases of the central nervous system, peripheral nerves, autonomic nervous system, and muscles; epilepsy; and inflammatory diseases such as multiple sclerosis. Central to the book are the lucid structuring of complex contents allowing efficient learning, even without prior knowledge of the subject; and the vital link between theory and clinical practice, with essential information on history-taking, the clinical examination, and additional tests, all supported by informative graphics and appropriate computed tomography or magnetic resonance imaging studies. Key Features: - Brilliant format and structure, making the assimilation of complex information easy and efficient - Clear color illustrations and graphics, many new or revised for the second edition - Comprehensive tables expand and organize information on many topics - New to the second edition: complete revision of contents and an enhanced layout - Vast clinical experience of two highly respected university teachers Fundamentals of Neurology: An Illustrated Guide is the ideal introduction to clinical neurology for medical students, physical therapists, and other professionals involved in patient care"--Provided by publisher.